Evaluating the Success of the Mobile JKN Application through the DeLone & McLean Framework - Lintang Firdaus; Arista Pratama; Anita Wulansari (bit-Tech, 2025)
The JKN mobile app is a digital platform developed by BPJS Kesehatan to help users access information and manage their membership independently. This research assesses the effectiveness of the application by employing the framework developed by DeLone and McLean, which includes aspects such as the quality of the system, the quality of information, the quality of service, and the intention to use, User Contentment, and Overall Gains. A quantitative approach was used, applying PLS-SEM for data analysis. Based on the Lemeshow formula, the minimum sample size was 384, and 400 active users of the latest app version participated. The analysis was conducted utilizing SmartPLS 4. Results show that the quality of the system and the quality of the information significantly influence user contentment and their inclination to participate. Thus, user contentment is essential in determining the perceived overall advantages. The study indicates that the app's success is more influenced by technical performance and user experience rather than service quality. This highlights the need to improve system reliability, interface usability, and information accuracy. Users tend to value fast access and functionality over support services. Continuous improvement in these areas can help increase satisfaction and long-term usage. The findings suggest that focusing on user-centered design and regular updates will strengthen digital health engagement. These insights can also serve as guidance for similar e-health initiatives in developing countries.